PESAN MORAL KEGIGIHAN DALAM ANIME GIN NO SAJI (SILVER SPOON) : ANALISIS SEMIOTIKA ROLAND BARTHES - Gusmayana, Gusmayana; Rahayu, Nana; Budiani, Dini (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The moral message of persistence in the anime Gin no Saji (Silver Spoon) Roland Barthes' semiotic analysis can contribute to the development of knowledge, especially for Japanese language learners by providing additional knowledge about anime, Roland Barthes' semiotic concept, and the moral message of persistence so that it can be realized in everyday life. day. The purpose of this study is to describe what moral messages describe persistence in verbal and non-verbal communication in the anime. The method used is observation, listening technique, note-taking technique and literature study. The results of the analysis show that there are five moral messages that describe persistence based on verbal communication and three moral messages that describe persistence based on non-verbal communication from characters in the anime Gin no Saji (Silver Spoon) based on Roland Barthes’s semiotic analysis.Key Words: The Moral Message, Persistence, Anime, Semiotic, Gin no Saji.